Analisis Pelayanan Pegawai Administrasi dalam Pengurusan Administrasi Kependudukan di Kantor Desa Medan Estate - Telaumbanua, Fobaso Cordias Putra; Yolanda, Agnita; Simamora, Beltahmamero (Universitas Medan Area, 2025)
This article or writing aims to find out how population administration services in Medan Estate village. The problem is focused on village employees and village communities. The benefit of this research is to make it easier for the community to manage and create population data. This study uses a descriptive method of qualitative approach by conducting direct interviews with village employees and village communities. The research resource persons were 4 people consisting of 3 employees of the Medan Estate village office and 1 person was a community domiciled in Medan Estate. The results of this study conclude that population administration is less than optimal. Although the service procedures are good, the service time is relatively fast, the service fee is free, the service products are useful, the facilities and infrastructure are adequate, the availability of the competence of the service officers, but it is still found that the human resources are very limited so that the ratio of the number of applicants who enter is not balanced with the existing officers. In addition, there is a lack of socialization from the government to the community, and there are still people who have not taken care of their population administration. Therefore, the results obtained through this study can be used as a reference and recommendation to support the smooth running of population administration services.